Convergence of a smoothing algorithm for horizontal linear complementarity problem with a nonmonotone line search - Zhao, Na; Fang, Yu (Optimization, 2025)
In this paper, we present a nonmonotone smoothing Newton type algorithm for solving the horizontal linear complementarity problem. We show that the proposed algorithm is globally convergent under an assumption that $ \{M,N \} $ { M , N } has the column $ \mathcal {W} $ W -property. Such an assumption is weaker than those required by most other smoothing Newton algorithms. The preliminary numerical results are reported.